DEVELOPMENT OF KNOWLEDGE, PERCEPTIONS, AND PUBLIC ATTITUDES QUESTIONNAIRE FACING THE ERA OF COMPULSORY HALAL MEDICINE CERTIFICATION - Ahmad Azrul Zuniarto; Nurkhasanah Mahfudh; Dyah Aryani Perwitasari; Siti Pandanwangi (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
A questionnaire is an instrument used to collect data from several people or respondents through a set of questions to be answered. The validity and reliability of the questionnaire describe how well the preparation of the questionnaire was related to the measurement scale. Reliability indicates that the questionnaire is consistent when repeatedly used. This study aimed to obtain a valid and reliable questionnaire on community knowledge, perceptions, and attitudes toward halal drugs.  The reliability of the knowledge questionnaire, perceptions, and attitudes was defined using  Cronbach's alpha. This cross-sectional study was conducted online from January to February 2023, with 600 respondents in six provinces on Java Island. The knowledge questionnaire validation test used Point Biserial, perception, and attitude of using the Pearson Product Moment. The majority of respondents were aged <25 years (73%), the dominant last level of education was the secondary level (66.5%), and most of the jobs were students (38.7%). The r value of the knowledge domain obtained is (0.209-0.662) which was greater than the r table (0.080) and met the validity criteria, the perception domain (0.471-0.764), and the attitude domain (0.250-0.757) which is greater than the r table and satisfies the validity criteria. The Cronbach’s alpha value of the knowledge domain obtained was 0.730, that of the perception domain was 0.756, and that of the attitude domain was 0.723, which was > 0.6 and meets the reliability criteria...